EU CONSTITUTIONAL LAW-POLICY MAKING AND THE NOTION OF “COMMON EUROPEAN LEGAL TRADITION” - Vittorio Olgiati (Passagens. Revista Internacional de História Política e Cultura Jurídica, 2011)
Leafing through a variety of EU official documents, it becomes apparent that, among the communicative strategies officially enunciated to s upport EU processes and policies, a special relevance has been ascribed to the notion o f a “common European legal tradition.” Indeed, reference to a “shared” and “settled” socia l, institutional and cultural context has been conceived of as a refined way to provide valid ity, legitimacy and social appeal to a quite recent geopolitical governance system such as that of European unionism. It is a fact, however, that, in spite of the authoritativen ess of EU official statements, an important debate continues at the scientific level about the actual existence and/or consistency of such a “common legal tradition,” due to either dive rging historical socio-legal developments in the various EU member states or the novelty of EU legal constructionism. The aim of this paper is to deal precisely with thi s issue by focusing on the way in which an extraordinarily (explicitly and implicitly) selecti ve mixture of old and new legal tools has been applied in order to portray the EU as an histo rically settled constituency. Accordingly, the most important EU normative steps towards EU co nstitutionalisation will be discussed and critically compared to previous – modern, pre-m odern and ancient – European constitutional experiences.